Percutaneous transhepatic interventional therapy of portal vein stenosis in paediatric liver transplantation: A systematic review of efficacy and safety. (1st November 2021) - Kyaw, Lin; Lai, Nai Ming; Iyer, Shridhar Ganpati; Loh, Dale Ser Kheng Lincoln; Loh, Stanley Eu Kuang; Mali, Vidyadhar Padmakar
Abstract: Purpose of the systematic review: To determine the efficacy and safety of percutaneous trans‐hepatic balloon and/or stent angioplasty (PTA) in the management of portal vein (PV) stenosis following paediatric liver transplantation. Methods: Articles were included from a systematic search of Medline, Embase, Cochrane CENTRAL, ClinicalTrials.gov and International Clinical Trials Registry from inception to the 29th of August 2020. Results: There were 213 paediatric liver recipients who underwent PTA for PV stenosis in 19 included studies published between 1991 and 2019. Balloon angioplasty was the initial treatment in the majority ( n  = 153). Primary stent placement ( n  = 34) was performed for elastic recoil, intimal tears and PV kinks and rescue stent placement ( n  = 14) for recurrent PV stenosis following primary balloon angioplasty. The technical success was 97.6%–100% overall, 97.6%–100% for balloon‐angioplasty‐only and 100% for primary stenting. The clinical success was 50%–100% overall, 50%–100% for balloon‐angioplasty‐only and 100% for primary stenting. Long‐term PV patency was 50%–100% overall, 37.5%–100% for balloon‐angioplasty‐only and 100% for primary stenting. Primary balloon angioplasty was successful in 78% of the cases. Of the recurrent PV stenoses, 9% resolved with stent placement and one required a meso‐Rex shunt. There was one re‐transplantation without stenting. The complication rate was 2.6% for balloon‐angioplasty‐only (bleeding, liver abscess, 2 PV thromboses) and 5.9% for primary stenting (bleeding, stent‐fracture). There was no procedure‐related mortality. Conclusion: Percutaneous transhepatic balloon angioplasty may be the initial management of portal vein stenosis in paediatric liver recipients. Stent placement may be a primary option in selected cases and a reliable rescue option for recurrent portal vein stenosis following balloon‐angioplasty‐only.